Electrode/electrolyte additives for practical sodium-ion batteries: a mini review. Issue 1 (5th December 2022) - Huang, Zhi-Xiong; Zhang, Xue-Li; Zhao, Xin-Xin; Zhao, Yuan-Yuan; Aravindan, Vanchiappan; Liu, Yu-Hang; Geng, Hongbo; Wu, Xing-Long
Abstract : Problems of practical sodium-ion batteries. Abstract : Electrical energy storage systems have attracted immense attention to the rapid development of intermittent renewable energy sources. Lithium-ion batteries (LIBs) have achieved unbelievable success, having been applied in mobile electronic devices for the last few decades and conquered the electric vehicles market. However, the cost of lithium is increasing, and its availability, in the long run, is a big question. In this line, a variety of systems beyond LIBs are proposed. Amongst them, sodium-ion batteries (SIBs) stand out owing to the sodium resources and the similar kind of "rocking chair" mechanism compared with LIBs. The development of cathodes and anodes for SIBs has reached a bottleneck. For practical applications, additives are vital and are the most effective and economical methods for enhancing the actual performances of batteries. In addition, additives also can improve the safety of SIBs remarkably. In general, electrolyte additives are widely explored owing to their ability to stabilize the formation of the solid electrolyte interphase (SEI) and the cathode electrolyte interphase (CEI). At the same time, the formation of SEI and CEI layers needs abundant Na ions during the charge–discharge process. A small amount of suitable additive can bring vast, salient benefits to SIBs. Thus, this review focuses not only on the role of electrolyte additives with the properties of the formation of stable SEI and CEI but also on improving the cycling life, thermal stability, and safety.